The Impact of Transitional Movements and Non-Manual Markings on the Disambiguation of Locally Ambiguous Argument Structures in Austrian Sign Language (ÖGS). (December 2019) - Krebs, Julia; Wilbur, Ronnie B.; Alday, Phillip M.; Roehm, Dietmar
Previous studies of Austrian Sign Language (ÖGS) word-order variations have demonstrated the human processing system's tendency to interpret a sentence-initial (case-) ambiguous argument as the subject of the clause ("subject preference"). The electroencephalogram study motivating the current report revealed earlier reanalysis effects for object-subject compared to subject-object sentences, in particular, before the start of the movement of the agreement marking sign. The effects were bound to time points prior to when both arguments were referenced in space and/or the transitional hand movement prior to producing the disambiguating sign. Due to the temporal proximity of these time points, it was not clear which visual cues led to disambiguation; that is, whether non-manual markings (body/shoulder/head shift towards the subject position) or the transitional hand movement resolved ambiguity. The present gating study further supports that disambiguation in ÖGS is triggered by cues occurring before the movement of the disambiguating sign. Further, the present study also confirms the presence of the subject preference in ÖGS, showing again that signers and speakers draw on similar strategies during language processing independent of language modality. Although the ultimate role of the visual cues leading to disambiguation (i.e., non-manual markings and transitional movements) requires further investigation, the present study shows that they contribute crucial information about argument structure during online processing. This finding provides strong support for granting these cues some degree of linguistic status (at least in ÖGS).